Parent commissioners’, elected commissioners’, and directors’ perceptions of parental participation in school board decision-making in Quebec - Ahehehinnou, Patrice Cyrille; Anne, Abdoulaye (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2023)
The purpose of this article is to understand the perceptions of parent commissioners, elected commissioners, and principals on the political participation of parents in the decision-making process within the councils of commissioners since the adoption of Bill 105 amending the Education Act. A multiple case study was conducted with two school boards in the City of Québec area, and semi-structured interviews were held with 13 participants. A content analysis of the data revealed that greater numbers and the right to vote have brought parent commissioners more legitimacy and recognition, as well as a more egalitarian relationship with the other members of the school governing bodies. The role of parent commissioners is now more decision-making than simply advisory.